Global gender gap report 2021 (World Economic Forum, 2021)
Another generation of women will have to wait for gender parity, according to the World Economic Forum’s Global Gender Gap Report 2021. As the impact of the COVID-19 pandemic continues to be felt, closing the global gender gap has increased by a generation from 99.5 years to 135.6 years.
Keywords: OFDIG; approches et analyses; covid-19; discipline; inégalités; périodes historiques; ressource en ligne; sciences de la gestion; systèmes d'oppressions; économie; égalité des sexes

La charge mentale, une double peine pour les femmes - Flèche, Sarah; Sénécal, Laura (CNRS Le journal, 2021)
Une étude menée par des économistes analyse comment la charge mentale que les femmes subissent encore majoritairement aujourd’hui ne leur permet pas de concilier équitablement vie professionnelle et familiale et nuit à leur bien-être. Un billet à lire sur le blog de la revue Dialogues économiques.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; charge mentale; discipline; inégalités; inégalités hommes-femmes; projet charge mentale; périodes historiques; ressource en ligne; sciences de la gestion; systèmes d'oppressions; thématiques; travail; travail domestique; économie

The future of diversity - Kuptsch, Christiane; Charest, Éric (International Labour Organization, 2021)
In this collection, scholars and practitioners reflect on the most appropriate interventions to create a more inclusive labour market for all. They explore the economic case for diversity and diversity management strategies, finding that diversity and inclusion must go hand in hand. The book also sheds light on the policy dilemma between respecting individuals and countering structural inequalities, which often requires categorization into groups. The authors remind us that there is diversity within diversity: not everyone receiving the same label has the same needs. The book covers a range of issues including gender equality and mainstreaming, migration and ethnic diversity, racism, violence against LGBTI people and age discrimination. It is thus a rich source of inspiration for anyone wishing to move towards greater justice in the labour market.
Keywords: approches et analyses; discipline; identités LGBTQIA2+; inégalités; justice sociale; racisme; rapport; sciences de la gestion; sexisme; systèmes d'oppressions; thématiques; économie